Effect of three safeners on sulfur assimilation and iron deficiency response in barley (Hordeum vulgare) plants. Issue 1 (10th May 2016) - Bartucca, Maria Luce; Celletti, Silvia; Astolfi, Stefania; Mimmo, Tanja; Cesco, Stefano; Panfili, Ivan; Del Buono, Daniele
Abstract: BACKGROUND: Safeners are agrochemicals used in agriculture to protect crops from herbicide injuries. They act by stimulating herbicide metabolism. As graminaceous plants, to cope with iron (Fe) deficiency, activate sulfur (S) metabolism and release huge amounts of Fe‐chelating compounds, or phytosiderophores (PSs), we investigated, in barley plants ( Hordeum vulgare, L.) grown in Fe deficiency, the effects of three safeners on two enzymes of S assimilation, cysteine (Cys) and glutathione (GSH), and PS release. Finally, we monitored the root Fe content in plants treated with the most effective safener. RESULTS: Generally, all the safeners activated S metabolism and increased Cys and GSH contents. In addition, the safened plants excreted higher levels of PSs. Given that mefenpyr‐diethyl (Mef) was the most effective in causing these effects, we assessed the Fe concentration in Mef‐treated barley and found higher Fe levels than those in untreated plants. CONCLUSION: The three safeners, in different ways but specifically, activated S reductive metabolism and regulated Cys and GSH contents, PS release rate and Fe content (Mef‐treated barley). The results of this research provide new indications of the biochemical and physiological mechanisms involved in the safening action. © 2016 Society of Chemical Industry